Genotyping of broiler-originated Campylobacter jejuni and Campylobacter coli isolates using fla typing and random amplified polymorphic DNA methods - Ertas, HB; Çetinkaya, B; Muz, A; Öngör, H (Elsevier Science Bv, 2004)
Liver and intestine samples taken from 200 broilers at 20 flocks were inoculated onto Preston Enrichment broth and agar for selective isolation of Campylobacter jejuni and Campylobacter coli. The isolates were identified by both conventional and polymerase chain reaction (PCR) methods. Campylobacter spp. were identified in 102 of 400 samples (200 liver and 200 intestine), 57 (14.25%) of which were identified as C. jejuni and 45 (11.25%) as C. coli. PCR-restriction fragment length polymorphism (RFLP) of the flagellin gene (flaA) and random amplified polymorphic DNA (RAPD) typing were used to describe the heterogeneity among amplified DNA products of C. Jejuni and C coli isolates. Flagellin gene analysis by RFLP of the isolates produced seven different band profiles. On the other hand, five distinct band profiles were obtained in the examination of the isolates with RAPD assay using a random primer (OPA-11). The results of this study demonstrated that a relatively low heterogeneity existed among C jejuni and C. coli strains isolated from the commercial broiler flocks in eastern Turkey. In the comparison of both typing methods, fla typing provided more discrimination than the RAPD assay used. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: Campylobacter jejuni; Campylobacter coli; PCR; fla; RFLP; RAPD; broiler